Strategi Komunikasi Kos Crisis Center Terhadap Anak Kos dan Induk Semang Dalam Berkontribusi Mempertahankan Predikat Yogyakarta Sebagai Kota Pendidikan - Sugiyanto Sugiyanto; Yenni Sri Utami (Jurnal Paradigma, 2013)
Kos crisis center is a social derivative organization of PKK Movement Team of Municipal Government Yogyakarta to conduct a mediation between dorm members, dorm house owner (landlord), community members and the municipal government. KCC has the abilities to accumulate the dorm member, landlady, local communities and governments by using communication strategy that is easily understood by the stakeholders, therefore, in social encounter they can form the structure, system and social reproduction. The relation between dorm member, landlady, local communities and the government has been crystallized in a form of mutual empowerment and become a force that has contribution in preservation of status of Yogyakarta as a city of education, city tourism, town and city of cultural tolerance.